Systemic Lupus Erythematosus in pregnancy - a multidisciplinary approach to family planning and adverse outcomes prevention - Aleksandra Nowak; Anita Janus; Dawid Łoś; Agata Kaptur; Dawid Dziedziński (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose Systemic Lupus Erythematosus is a chronic multisystemic autoimmune disease with periods of remissions and flares [1,5,25]. Because of its possible consequences and unpredictability, it is undoubtedly an issue for such patients to decide about pregnancy [3].  The main aim of this review is to present the possible risks of SLE in pregnancy, its general management and current recommendations regarding pregnancy planning and pre-/postnatal care.  Review Methods   For the review we conducted research of scientific literature from PubMed and books, applying the keywords (below). Consequently, we included in our references above 20 selected articles published between 2017-2024 and 3 chapters of different medical books. All of these were analyzed in terms of their currency and relevance.   A brief description of the State of Knowledge   SLE mostly affects women at the reproductive age [2, 3,5]. It often requires long-term therapy that aims to achieve and maintain an inactive stage by means of numerous aggressive drugs. Its proper management in gestation is even more challenging than usually, owing to the increased risk of adverse pregnancy outcomes (APO) and higher maternal mortality [1,2,4,5,7]. Therefore, to achieve successful pregnancy, risk stratification, therapy modification and individually adjusted plan of follow-up visits are the most crucial conditions to be met [1,6,7,13].    Summary   Considering all the potential complications that may occur in general, the issue of family planning should be raised with every female patient [5,6]. The key to the best outcomes is proper implementation of current strategies and empowering the patient to be an active and aware participant in the decision-making process [1,3,4,6,11].